Magnetic Resonance Imaging on Patients with Implanted Cardiac Pacemakers - Seitz, Sebastian (Karlsruhe transactions on biomedical engineering / Ed.: Universität Karlsruhe (TH) / Institute of Biomedical Engineering, 2011)
The aim of this work was to identify the patterns that can induce heating around implanted cardiac pacemakers during MRI and to develop strategies to counteract them. Two approaches were taken: computer simulations of the occurring electromagnetic field distributions and in-vitro experiments using phantoms in real MRI devices, both for conventional bore-hole and new open MRI systems. Using the open MRI, the observed heating could be reduced significantly.